Strategi Guru Dalam Meningkatkan Pemahaman Soal Matematika Siswa Kelas V: Studi Kualitatif Di SD Negeri Simawang - Beti Asyriah; Aprilia Wulandari; Safrizal Safrizal; Gustina Gustina; Syaiful Marwan (Lembaga Riset Ilmiah, 2026)
This study aims to analyze the strategies used by teachers to improve fifth-grade students' understanding of mathematics problems at Simawang Public Elementary School. The study employed qualitative methods with a descriptive approach. Data were collected through interviews, observations, and documentation, then analyzed using the steps outlined by Miles and Huberman: data reduction, data presentation, and conclusion drawing. The results indicate that teachers implemented several key strategies: 1) supplementary classroom guidance for students who were unable to follow the lesson; 2) utilizing Smart TVs as interactive learning media that combined visuals, audio, and simulations; and 3) interactive learning through educational games, such as tug-of-war and open the box. These strategies have been shown to improve students' understanding of mathematics problems, increasing their motivation, active participation, and emotional engagement. Furthermore, collaboration between teachers and the principal and community leaders, and the use of appropriate teaching methods, strengthened the effectiveness of learning. These findings demonstrate the importance of integrating academic strategies, interactive media, and emotional support in improving the quality of mathematics learning at the elementary level.